A new genus and species of tribe Macrosiphini (Hemiptera, Aphididae) from northeast China - Stekolshchikov, Andrey V.; Ge-Xia, Qiao (Zootaxa, 2008)
Brevisiphonaphis hirsutissima gen. nov., sp. nov. is described from specimens collected in northeast China on Artemisia argyi H.Lév. & Vaniot (Asteraceae). The genus is illustrated with the biometric data for apterous viviparous females. This aphid genus is closely related to Microsiphum Cholodkovsky, 1902 and Microsiphoniella Hille Ris Lambers, 1947. Type specimens are deposited at the Institute of Zoology, Chinese Academy of Sciences, Beijing, China, and at the Zoological Institute, Russian Academy of Science, St. Petersburg, Russia.